Inclusive Education at Islamic and General Universities: An Analysis of Policies, Teaching Strategies, and Curriculum Implementation - Zulkipli Lessy; Abd Rachman Assegaf; Sangkot Sirait (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2021)
AbstractThis study recruited participants from UIN Sunan Kalijaga and Universitas Sanata Dharma in Yogyakarta and the University of Sydney, and the University of Western Sydney in Australia and aimed at investigating whether policies are implemented as a bridge to accommodate disabled students for admission and academic pursuits. In this combined policy research and case study, individual, group, and policymaker interviews were conducted. The findings indicate that, while university policymakers admit students with special needs, a lack of academic advocates among faculty has hampered understanding of pertinent policies. As a result, some lecturers do not pay attention to inclusiveness. There are environmental impediments, a dearth of services throughout the enrollment process, a lack of faculty competencies, and a paucity of information in syllabi indicating where impaired students can access resources. In Australia, colleges are more forthright about accommodating students with special needs during the enrolling process and during class time. Both campuses have disability assessment clinics. However, some are more physically and centrally positioned to facilitate impaired students who self-refer for services. The purpose of this paper is to argue that genuinely inclusive education is not segregated schooling that separates 'normal' pupils from those with special needs. For authentic inclusion, disabled populations require considerate, if not extraordinary, care and services. AbstrakPenelitian ini merekrut partisipan di UIN Sunan Kalijaga dan Universitas Sanata Dharma di Yogyakarta serta University of Sydney dan University of Western Sydney di Australia dan bertujuan untuk investigasi apakah kebijakan sebagai sarana untuk mengakomodasi mahasiswa difabel pada proses pendaftaran dan pencapaian akademik. Penelitian kebijakan dan studi kasus ini dilakukan melalui serangkaian interview dengan individu, kelompok, pembuat kebijakan. Hasil penelitian menunjukkan bahwa meskipun para pengambil kebijakan menjamin penerimaan mahasiswa dengan kebutuhan khusus, lemahnya dukungan para pengajar telah mengurangi perhatian penerapan kebijakan yang relevan. Akibatnya, beberapa pengajar kurang menaruh perhatian pada inklusivitas. Terdapat halangan lingkungan, kurangnya layanan selama proses pendaftaran dan kompetensi para pengajar, serta kurangnya petunjuk dalam silabus menjelaskan dimana mahasiswa difabel mengakses sumber-sumber yang diperlukan. Kampus-kampus di Sydney lebih transparan dalam memfasilitasi mahasiswa difabel selama proses pendaftaran dan kuliah. Terdapat banyak pusat layanan, beberapa secara struktural terpusat di kampus untuk diakses. Artikel ini berargumentasi bahwa pendidikan inklusif itu bukan sistem kelas yang memisahkan mahasiswa ‘normal’ dari yang berkebutuhan khusus. Untuk inklusi, mahasiswa difabel perlu digandeng dan mendapatkan pengajaran dan layanan yang memadai.How to Cite: Lessy, Z., Assegaf, A. R., Sirait, S. (2021). Inclusive Education at Faith-Based and Non-Faith Based Universities: A Policy, Teaching, and Curriculum Analysis. TARBIYA: Journal of Education in Muslim Society, 8(1), 1-15. doi:10.15408/tjems.v8i1.18992.